Characterization of the activities developed by retired professors of Universidad Nacional de Colombia (2012)
Al formar parte del recurso humano de las Universidades, los docentes entran a ser parte importante del capital intelectual de las mismas al ser gestores y transmisores del conocimiento. Pero, se debe tener en cuenta que como seres humanos, pasan por distintas etapas en su ciclo de vida y que a lo largo de su historia van adquiriendo una trayectoria profesional, la cual al momento de la jubilación puede representar un capital invaluable, que por ende puede seguir siendo útil para la sociedad. Es en este punto donde surge el interrogante ¿A qué se dedican los docentes luego de la jubilación? Esta pregunta cobra validez dentro de la Universidad Nacional de Colombia debido a la consciencia que se tiene de la importancia, el potencial y creatividad de este grupo de docentes. El objetivo de este trabajo es presentar una propuesta metodológica para la caracterización y análisis de las actividades profesionales realizadas por los docentes jubilados de las Instituciones de Educación Superior –IES-, en primer lugar, a partir de la revisión bibliográfica de los diferentes modelos de ciclo de vida profesional y la trayectoria científica de los docentes, y en segundo lugar, a partir del análisis de estudios realizados en Universidades Norteamericanas y Europeas, los cuales se centran en el análisis de las características personales y profesionales de dicho grupo de personas. Lo anterior, como base para poder determinar papel de los docentes jubilados como parte del capital intelectual de las Instituciones de Educación Superior más importantes en el contexto colombiano, la Universidad Nacional de Colombia –UNAL-. / Abstract. As a part of the Human Capital of the Higher Education Institute, professors come to play an important role acting as creators, managers and knowledge transmitters. However, as human beings they cross different stages in their life cycle and during that process, they acquire a professional and scientific career that at the retirement moment could become an invaluable capital that could continue being useful to the society. Is at this point when we ask ¿What do the professors do after their retirement? This question become relevance inside one of the most important Higher Education Institute in the Colombian context because of the awareness that it has on the importance, potential and creativity of this group of academics. Another reason is related with using a model for measuring research capabilities of this Higher Education Institute based on Intellectual Capital approach, the retired professors and their legacy as a reiterative subject. The objective of this work is based on building of a methodological proposal for the characterization and analysis of the professional activities developed by the retired professors of the Higher Education Institutions; characterize the activities developed by retired professors of Universidad Nacional de Colombia -UNAL at national level between 2001 and 2011. This based on the one hand, on a bibliographical review of studies done in different North America and United Kingdom Universities which are focused in the analysis of the personal and professional characteristic, also in the analysis of the different professors life-cycle models, and on the other hand, a the current model of the institution for measuring research capabilities based on Intellectual Capital approach. The previous will be the base to determine the role of retired professors as a part of the Intellectual Capital of the Higher Education Institutions and to have inputs for design and follow-up research policies related with retired professors.